From Energetics to Ecosystems: The Dynamics and Structure of Ecological Systems - Rooney, Neil.; McCann, K. S.; Noakes, D. L. G.; SpringerLink (Online service) (Dordrecht : Springer Netherlands, 2007)
Ecosystems are complex and enigmatic entities that are ultimately our life support systems. Understanding these systems to the point of being able to predict their behaviour in the face of perturbations requires that researchers adopt a number of strategies that vary in both approach and scale. This book, in a sense, is representative of some of the developments that have unfolded when math and physics met ecology. Here, some of the world's leading ecologists examine ecosystems from theoretical, experimental, and empirical viewpoints, from energetics to ecosystems. The book begins with simplifying and synthesizing nature's complex relationships. It then moves on to explore the mapping between food web structure and function and ends with the role of theory in integrating different research areas. From the breadth of systems analyzed to the rigor of approaches taken, this book is not only a useful resource for students and researchers in ecology, but also serves as a fitting tribute to the life and work of Peter Yodzis.
SECTION I -- A Process-Oriented Approach to the Multispecies Functional Response -- Homage to Yodzis and Innes 1992: Scaling up Feeding-Based Population Dynamics to Complex Ecological Networks -- Food Webs, Body Size and the Curse of the Latin Binomial -- An Energetic Framework for Trophic Control -- SECTION II -- Experimental Studies of Food Webs: Causes and Consequences of Trophic Interactions -- Interplay Between Scale, Resolution, Life History and Food Web Properties -- Heteroclinic Cycles in the Rain Forest: Insights from Complex Dynamics -- Emergence in Ecological Systems -- Dynamic Signatures of Real and Model Ecosystems -- SECTION III -- Evolutionary Branching of Single Traits -- Feedback Effects Between the Food Chain and Induced Defense Strategies -- Evolutionary Demography: The Invasion Exponent and the Effective Population Density in Nonlinear Matrix Models -- Of Experimentalists, Empiricists, and Theoreticians.
Keywords: LIFE SCIENCES; ECOLOGY; BIODIVERSITY; ENDANGERED ECOSYSTEMS; LIFE SCIENCES; ECOLOGY; THEORETICAL ECOLOGY/STATISTICS.; BIODIVERSITY; ECOSYSTEMS